Prospects for the use of donor blood components in the treatment of COVID-19 patients - E. I. Lazareva; S. V. Pavlenko (Вестник хирургии имени И.И. Грекова)
INTRODUCTION. The significance of all components of donor plasma on the process of inflammation in patients with COVID-19 is currently a little-studied problem.The OBJECTIVE was to determine the effect of components of donor plasma on the inflammatory process in COVID-19.METHODS AND MATERIALS. The study included 50 patients with coronavirus infection (COVID-19), bilateral polysegmental pneumonia, who received standard therapy. Anticovid plasma transfusions were performed in 38 patients. Quarantine fresh frozen plasma was transfused to 12 patients. Before and after transfusion, changes in biochemical, immune, clinical and instrumental parameters of patients were evaluated in dynamics. Separately, the intensity of humoral immunity to SARS-CoV-2 was evaluated in donors of anticovid plasma and in all patients in dynamics. The dynamics of changes in the parameters of components of donor plasma was studied with an assessment of their correlation relationships between biochemical and immune blood parameters before and after transfusion. The most significant component of donor plasma affecting the inflammatory process in COVID-19 was identified.RESULTS. After transfusion of any type of donor plasma, the parameter of the intensity of humoral immunity to SARS-CoV-2 increased with normalization of clinical and instrumental parameters and a decrease in the parameters of acute phase inflammatory reactants. The value of the alpha2-macroglobulin index was reduced, and it increased after transfusion. Correlations between acute phase inflammatory reactants and donor plasma components before and after transfusion with any type of donor plasma were consistently studied. As a result, the interrelations of varying degrees of severity with the alpha2-macroglobulin index were revealed.CONCLUSION. After transfusion of any type of donor plasma, there is an increase in the intensity of humoral immunity to SARS-CoV-2 in the form of the appearance of specific antibodies, the parameters of acute phase inflammatory reactants decrease. One of the significant components of donor plasma affecting the inflammatory process in COVID-19 is alpha2-macroglobulin. The study of the possibility of using alpha2-macroglobulin isolated from donor plasma is one of the promising directions in the complex treatment of COVID-19 patients.